Design in motion applying design principles to filmmaking - Hilton, Penny (Bloomsbury Academic, 2020)
With an abundance of information on how to create motion graphics already available, Design in motion focuses on the why of moving image and less about the how. By unpacking the reasons behind screen designer's production choices, each chapter deconstructs examples of motion graphics by drawing on case studies of both familiar examples from contemporary cinema and unseen work from postgraduate motion graphic designers. It examines the value of image, text, motion, camera and transitions, explaining on detail why some methods works, while others fail.